Solution for Shiny Specular 3D Mechanical Surface Measurement using Combined Phase Shift and Gray Code Light Projection - Nguyen, Thi Kim Cuc; Nguyen, Van Vinh; Nguyen, Thanh Hung (Old Journal, 2019)
Non-contacts 3D shape measurement has been widely studied and applied to many advantages in terms of speed, accuracy and ease of implementation. However, the measuring system is still limited when measuring surfaces with high reflectivity by the optical signal cannot be obtained correctly. This paper proposes a new approach to solve the problem of measuring mechanical surface with high implementation. The appropriate exposure times in each region of the histogram are determined, then point clouds are merged at appropriate exposure times to obtain a good quality point cloud to avoid the saturation region on the CCD. Two different aluminum surfaces profile parts are measured with using single exposure time and proposed solution. Experimental results prove that the proposed solution can inspect the 3D surface of the mechanical parts with high surface reflectivity.